IS AZO-COUPLING OF P-NITROTHIOPHENOL A GOOD REACTION FOR THE EVALUATION OF PLASMON CATALYSIS MECHANISM? - Gorbunova, Alina; Semyonov, Oleg; Postnikov, Pavel; Guselnikova, Olga (National Laboratory Astana, 2022)
The excitation of plasmon resonance on noble metals nanostructures delvers practical outcome in sensorics, photocatalysis. In plasmon-induced transformationsm, plasmon exciation allows to overcome the limitations of classical catalysis, such as high temperatures, pressures, and the use of complex catalytic systems. A model reaction for studying the mechanistic aspects of the plasmon-induced catalysis is the azo coupling of nitro- or -aminothiophenols. However, the nature of bonding between thiols and plasmonic metals is considered as chemisorption, which may be reversibile – one thiophenols can be replaced by other molecules.
Keywords: Type of access: Embargo; plasmon catalysis mechanism